Intuition and Experience - Patrick Lynch (Oz, 2009)
If words become disassociated from experience, and subjectivity is not encouraged towards communication, then the architectural imagination becomes disembodied and open to picturesque interpretations. Without words, we cannot think; if we do not draw we cannot see. Can ‘thinking and seeing as an architect’ manifest without insight and intuition?